Contrasting Effects of Lithium Chloride and CB1 Receptor Blockade on Enduring Changes in the Valuation of Reward - Hernandez, Giovanni; Bernstein, David; Schoenbaum, Geoffrey; Cheer, Joseph F. (Frontiers in Behavioral Neuroscience, 2011)
When an organism responds for a reward, its learned behavior can be characterized as goal-directed or habitual based on whether or not it is susceptible to reward devaluation. Here, we evaluated whether instrumental responding for brain stimulation reward (BSR) can be devalued using a paradigm traditionally used for natural rewards. Rats were trained to lever press for BSR; afterward, BSR was paired with either lithium chloride (LiCl, 5 mg/kg, i.p.), a pro-emetic, or AM251, a CB1 receptor antagonist (3 mg/kg, i.p.) or the vehicle of these compounds. Pairings of BSR with these compounds and their vehicles were performed in a novel environment so that only unconditional effects of BSR would be affected by the pharmacological manipulations. Subsequently, in a probe test, all rats were returned in the drug-free state to the boxes where they had received training and instrumental responding was reassessed in the absence of BSR delivery. When compared to control, LiCl produced a significant decrease in the number of responses during the test session, whereas AM251 did not. These results show that instrumental responding for BSR is susceptible to devaluation, in accord with the proposal that this behavior is supported at least in part by associations between the response and the rewarding outcome. Further, they suggest that reward modulation observed in studies involving the use of CB1 receptor antagonists arises from changes in the organism’s motivation rather than drug-induced changes in the intrinsic value of reward.